Modelo de calidad para la acreditación de carreras universitarias - Toro-Lira Pardo, Úrsula (2010)
The current Peruvian government passed law 28740 to create a number of organizations to regula te the processes of evaluation, accreditation, and certification of educational quality. In this paper the various organizations established by the Peruvian government, as well as their objectives and educational accreditation policies will be introduced, emphasizing on thestages of the accreditation process in universities, and the models for accrediting university careers. Finally, sorne ideas and criteria established by the Peruvian government for university careers will be presented.